Boundaries of empirical approaches in educational research (2023)
This paper critically reviews the research done in education faculties in Nigerian universities. This research, though categorized in postgraduate schools or colleges as mainly in the liberal arts/humanities and the social sciences, depends on the theories and methodologies from other disciplines. The arts and social sciences are disciplines where undergraduates in education take courses in teaching to earn bachelor’s degrees, the postgraduate level offers varied opportunities for educational research to maximize the uniqueness of mixed method research for education.